Determination of Flavonoid Content in Brazilian Propolis Extracts by UV-Vis Spectroscopy and PLS Regression - Ássimos, Ariane Araújo; Bernardes, Cristina Donizeti; Aleme, Helga Gabriela; Sanches Barbeira, Paulo Jorge (Current Analytical Chemistry, 2025)
<span class=
Keywords: flavonoids